David Castro Hussong and Jay Porter: The Baja California Cookbook. Exploring the Good Life in Mexico - Lord, Matt (Petits Propos Culinaires, 2020)
David Castro Hussong and Jay Porter: The Baja California Cookbook. Exploring the Good Life in Mexico: Ten Speed Press, 2020: 272 pp., hardback, £22.50.